Pengembangan buku ajar IPAS berbasis LVEP (living values education program) untuk meningkatkan sikap peduli lingkungan pada peserta didik Madrasah Ibtidaiyah - Rofiah, Tutik Dinur; Fauziyah, Dewi Nur Aini; Sari, Ananda Puspita (Universitas Sarjanawiyata Tamansiswa, 2026)
This study examines the development of teaching materials based on the Living Values ​​Education Program. This book contains how to internalize 12 life values ​​contained in the Living Values ​​Education Program concept in a science learning material at the Madrasah Ibtidaiyah level. This study aims to integrate the values ​​contained in the LVEP in science learning that is characterized scientifically. The research method in this study is research and development or R&D with the ADDIE approach. The development process includes planning, design, implementation, and evaluation of the textbook. The study was conducted in MI Al Falaah Manis Renggo class V with a total of 59 respondents. The level of product feasibility is measured by conducting product validity to the validation of teaching materials and materials experts. The average obtained percentage of 82,5%